UNDERSTANDING CONSUMER MIGRATION TOWARD NON-CASH PAYMENT SYSTEMS: A PUSH–PULL–MOORING PERSPECTIVE - Indarwati, Peni; Syaifuddin Fahmi; Catur Adi Pamungkas (Jurnal Ilmu Manajemen (JIMMU), 2025)
AbstractThe digital transformation in the financial sector has brought about significant changes in consumer behavior, one of which is the use of non-cash payment systems as a substitute for cash. This study aims to determine the role of perceived value, alternative product attractiveness, and digital literacy variables on consumer switching intentions. Digital literacy is considered to have a moderating role that strengthens the relationship between perceived value and alternative product attractiveness on switching intentions, this also provides a novelty that is expected to be obtained in the study of consumer switching behavior. This study uses a quantitative approach through a survey method. Data were collected from 200 respondents who were encountered incidentally while shopping at retail outlets in the Malang city area. The data collection instrument used was a structured questionnaire with indicators created through a literature review and synthesis of previous research results. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM), by evaluating the measurement and structural models in the study. The results show that perceived value has an influence that can encourage consumers to have switching intentions. On the other hand, the attractiveness of alternative products is also a motivating factor for consumers to switch to using non-cash payment systems, where the stronger the attractiveness of alternative products, the higher the desire to switch. Another finding is that digital literacy is a mooring factor that can strengthen and weaken the relationship between perceived value and alternative attractiveness on the intention to switch. This is a contribution of research results that can provide insight to the business world so that it does not only focus on product sales but also pay attention to the extent to which consumers have sufficient literacy about the technology used in the product. Thus, the results of this study indicate that consumer intention to switch is not only influenced by the value and attractiveness of alternative products, but also there is a role of digital literacy as a reinforcement.